TRANSFORMATION OF CORPORATE SOCIAL RESPONSIBILITY OF BUSINESS BASED ON CIRCULAR ECONOMY PRINCIPLES - Андрусів, Уляна Ярославівна; Зелінська, Галина Олексіївна (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2024)
The article examines the transformation of corporate social responsibility (CSR) in the context of transition to a circular economy, which becomes particularly relevant in the face of global environmental challenges and the need for sustainable development. The peculiarities of CSR development under Russia's full-scale invasion of Ukraine are revealed, where relevance, timeliness of decisions, and speed of their implementation become the main characteristics, necessitating the adaptation of existing approaches to new realities. It is determined that the implementation of circular economy principles into CSR practice creates new opportunities for solving social and environmental problems through the formation of closed production cycles, waste minimization, and efficient resource use. The relationship between circular business models and the effectiveness of corporate social initiatives has been analyzed, particularly in aspects of work comfort, social protection of personnel, and environmental sustainability of production activities, which revealed a synergistic effect from their combination. The current state of CSR development in Ukraine has been studied, revealing that the most active in this field are representative offices of foreign companies and national enterprises with innovation-oriented development strategies that implement advanced social responsibility practices and circular economy principles. An analysis of international experience in integrating circular economy principles into CSR strategies has been conducted, and possibilities for its adaptation to Ukrainian realities have been identified. Practical recommendations for improving regulatory framework and stimulating the development of socially responsible business in the transition to a circular economy are proposed, including mechanisms of state support, tax incentives, and public-private partnership development programs. The necessity of creating an integrated system for monitoring and evaluating the effectiveness of CSR initiatives in the context of achieving circular economy goals has been substantiated.